Hybrid algorithm based on improved extended shifting bottleneck procedure and GA for assembly job shop scheduling problem. Issue 9 (2nd May 2020) - Shi, Fei; Zhao, Shikui; Meng, Yue
Abstract : With the makespan as the optimisation goal, we propose a hybrid solving method that combines improved extended shifting bottleneck procedure ( i -ESB) and genetic algorithm (GA) for the assembly job shop scheduling problem (AJSSP). Hybrid genetic algorithm (HGA) uses a GA based on operation constraint chain coding to achieve global search and a local search based on an i -ESB. In the design of i -ESB, an extended disjunctive graph model (EDG) corresponding to AJSSP is presented. The calculation method of the operation head and tail length based on EDG is studied, as well as the searching method of key operations. The Schrage algorithm with disturbance is used to solve the single-machine scheduling subproblem. The selection criterion for bottleneck machines is increased. A greedy bottleneck machine re-optimisation process is designed. The effectiveness and superiority of the proposed algorithm are verified by testing and analysing the relevant examples in the literature.